FACTORS INFLUENCING THE SUCCESS OF TECHNOLOGY ADOPTION: A CASE STUDY OF INDONESIAN MANUFACTURING FIRMS - Ellitan, Lena (Jurnal Manajemen dan Kewirausahaan, 2004)
To date, the role of technology management as a factor of success in technological innovation has been a subject of significant interest among practitioners and academicians. Despite the plethora of attention given to the numerous issues of management of new technology adoption and implementation, many organizations still fail to manage their technology efficiently, effectively, and strategically. This paper is based on a field investigation via face to face interviews with top management in East Java involving medium and large manufacturing companies from the tobacco, plastic, pulp, furniture, textile, cable and plywood sectors. This research seeks to investigate the extent of technology adoption and its management in medium and large Indonesian manufacturing companies. Further, this study investigates the technology benefits perceived by respondents. The study found that: (1) Indonesian manufacturing companies still lack a strategic perspective when adopting technologies and they are more concerned with short-term issues; (2) they face problems related to people, organizational issues, limited budgets and lack of government support; (3) these problems limit the choice of technologies and together with the national economic situation, reinforces the short-term mindset of top management. In addition, the investigation of critical success factors and inhibitors of technology adoption is necessary for identification of a proper vision and strategic viewpoint of managing new technology.Abstract in Bahasa Indonesia : Sampai sekarang, peranan manajemen teknologi sebagai factor keberhasilan dalam inovasi teknologi menjadi topik yang menarik perhatian para praktisis maupun akademisi. Walaupun masalah-masalah manajemen teknologi dan implementasinya telah banyak diperhatikan, masih ada banyak perusahaan yang belum mampu mengatur teknologi secara efisien, secara efektif atau dengan strategi yang tepat. Makalah ini dibuat berdasarkan survei lapangan yang menggunakan wawancara langsung dengan para manajer atas di Jawa Timur dari perusahaan manufaktur besar dan menengah dari sektor rokok, kertas, mebel, tekstil, kawat, dan kayu lapis.Penelitian ini bertujuan untuk menyelidiki sampai sejauh mana teknologi telah diadopsi dan juga cara mengaturnya di perusahaan manufaktur yang menengah dan besar di Indonesia. Lebih lanjut, penelitian ini ingin mengetahui persepsi responden tentang keuntungan yang diperoleh dari teknologi. Penemuan penting: (1) perusahaan manufaktur di Indonesia masih belum mempunyai pandangan strategic terhadap adopsi teknologi and menjadi lebih berfokus pada masalah-masalah bersifat jangka pendek; (2) ada masalah terkait dengan sumber daya manusia, masalah organisasi, anggaran yang kecil, dan tidak didukung oleh pemerintah; (3) masalah-masalah tersebut menjadi kendala dalam memilih teknologi dan bersama dengan keadaan ekonomi nasional menyebabkan para manajer mempunyai pandangan jangka pendek. Selain itu, penelitian tentang faktor-faktor kritis yang membawa keberhasilan dan juga faktor-faktor yang menghambat adopsi teknologi harus ditentukan agar visi dan pandangan yang tepat terhadap teknologi baru dapat disusun.Kata kunci: adopsi teknologi, manufaktur, Jawa Timur, industry menengah/besar.